Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Hotel Fairuz Di Palangka Raya - Agau Lenin; Achmad Syamsudin (Jurnal Manajemen Sains dan Organisasi, 2020)
Purpose, - The purpose of this study was to determine and to know the effect of work motivation and discipline on employee performance at Fairuz Hotel in Palangka Raya.Design/methodology/approach - The research method used was qualitative, quantitative by using Multiple Linear Regression analysis techniques. The population and sample in this study were all of the Employees' Performance at Fairuz Hotel in Palangka Raya, totaling 30 people. Findings - This research shows the results partially (t-test): a) Motivation has significant and significant effect on Employee Performance, b) Work Discipline has a significant and significant effect on Employee Performance, and simultaneously the results of the study show Work Motivation and Discipline have a significant effect on Employee Performance in this study R2 = 0.532 or 53.2%.